Depression, Anxiety, Stress Correlated with Suicide Idea on Students of The Faculty of Health - Musfara, Deah Dwi; Wiwik Widiyawati; Widya Lita Fitrianur (Journal of Ners and Midwifery, 2024)
The occurrence of suicide in the world had never decreased, this started with the emergence of suicidal ideas, which originated from several mental and physical health disorders, but currently most of the younger generation, especially students, experiencing depression, anxiety, and stress which caused many students to choose to end their life due to various pressures during education. This research aimed to determine the correlation between depression, stress, anxiety, and suicide idea. This research was a study using a quantitative approach and a cross-sectional research design. The data collection used a questionnaire filling system involving 215 students from the Faculty of Health, University of Muhammadiyah Gresik, a significance value of 0.01 (p-value < 0.05) was obtained for each independent variable which was related to the dependent variable, this shown that depression, anxiety and stress were related to suicide idea. It could be concluded that depression, anxiety, and stress correlated with suicide idea at the Faculty of Health, University of Muhammadiyah Gresik. Psychological disorders that made students uncomfortable greatly influence the emergence of suicide idea. Thus, this needed to be resolved considering the correlation between depression, anxiety, stress, and suicide idea on students of the Faculty of Health, University of Muhammadiyah Gresik. Such as providing mental health care or counseling facilities that guarantee the safety or mental health of students with the aim of improving psychological health and minimizing the risk of suicidal ideation caused by depression, anxiety and stress